Design and characterisation of ex-situ bulk MgB2 superconductors containing a nanoscale dispersion of artificial pinning centres - Matthews, G; Liu, J; Grovenor, C; Grant, P; Speller, S (IOP Publishing, 2020)
MgB2 pellets containing a nanoscale dispersion of artificial pinning centres have been successfully manufactured through a powder metallurgy route based on the oxide dispersion strengthened (ODS) concept more usually used for steels and superalloys. Commercial MgB2 powder and Y2O3 nano-powder were mechanically alloyed in a high energy planetary ball mill and consolidated using the field assisted sintering technique. The composite powders were ball milled for different times up to 12 h and characterised by means of particle size analysis, x-ray diffraction (XRD) and scanning transmission electron microscopy (STEM). The microstructure and superconducting properties were characterised by density, XRD, STEM and magnetic property measurements. The powder microstructure comprised Y2O3 particles dissolved into the MgB2 matrix. After consolidation there was a near-uniform dispersion of precipitated YB4 and MgO particles. A bulk 0.5 wt% Y2O3-MgB2 composite showed the best superconducting performance with a significant improvement in J c at high field compared with unmodified MgB2, and only a small reduction in T c . The results suggest that the ODS concept is promising to improve the superconducting properties of MgB2.